What did we learn about ocean particle dynamics in the GEOSECS–JGOFS era?. (April 2015) - Jeandel, Catherine; Rutgers van der Loeff, Michiel; Lam, Phoebe J.; Roy-Barman, Matthieu; Sherrell, Robert M.; Kretschmer, Sven; German, Chris; Dehairs, Frank
Highlights: Compiling ∼180 references, a review of ocean particle dynamics knowledge is proposed. Time covered: from the early 50s to the beginning of 21th century (GEOSECS–JGOFS era). Origin, transport and fate of different size classes of particles are discussed. Limits of today's understanding and modeling of the particle dynamics are listed. Strategies for further studies of marine particles as part of GEOTRACES are given. Abstract: Particles determine the residence time of many dissolved elements in seawater. Although a substantial number of field studies were conducted in the framework of major oceanographic programs as GEOSECS and JGOFS, knowledge about particle dynamics is still scarce. Moreover, the particulate trace metal behavior remains largely unknown. The GEOSECS sampling strategy during the 1970s focused on large sections across oceanic basins, where particles were collected by membrane filtration after Niskin bottle sampling, biasing the sampling toward the small particle pool. Late in this period, the first in situ pumps allowing large volume sampling were also developed. During the 1990s, JGOFS focused on the quantification of the "exported carbon flux" and its seasonal variability in representative biogeochemical provinces of the ocean, mostly using sediment trap deployments. Although scarce and discrete in time and space, these pioneering studies allowed an understanding of the basic fate of marine particles. This understanding improved considerably, especially when the analysis of oceanic tracers such as natural radionuclides allowed the first quantification of processes such as dissolved-particle exchange and particle settling velocities. Because the GEOTRACES program emphasizes the importance of collecting, characterizing and analyzing marine particles, this paper reflects our present understanding of the sources, fate and sinks of oceanic particles at the early stages of the program.